Productive Structure and Income Distribution: the Brazilian Case. - Guilherme Moreira; Leandro De Oliveira Almeida; Joaquim Jose Martins Guilhoto; Carlos Roberto Azzoni (European Regional Science Association (ERSA), 2006)
This study deals with the impacts of structural changes on income distribution in Brazil in the period 1992-2002. A Pure Leontief Model and a Leontief-Miazawa Model were utilized to portray the structure of the economy in both years, and to perform counterfactual simulations on some important changes occurring during the period. The methodology allowed for the identification of the high and low inequality sectors in both years, and to their contribution to the increasing inequality during the period. It is interesting to notice that some sectors with low internal inequality ended-up provoking increased global inequality through their interaction pattern with other sectors in the economy,and through the consumption structure. The results also indicate that the change in sectoral shares in the period contributed to diminishing inequality. Therefore, the causes for increasing inequality remains within the distribution of wages within the sectors.
Keywords: 330